P5_4 Tatooine Habitability - Evershed, Mabel Elisabeth; Baldwin, Emily Jane; Cook, Naomi Esther; Beedle, Thomas James (Physics Special Topics, 2017)
In the Star Wars franchise, the main protagonist Luke Skywalker grows up on planet Tatooine, which is shown to orbit two G-type stars [1], Tatoo I and Tatoo II. We considered the orbit of the planet in three different positions relative to the twin suns, calculating the habitable zone for each, to conclude whether it is possible for this planet to exist in the habitable zone at all times. We found the range in which the planet can be in the habitable zone for its entire orbit: 1.42 - 1.90 AU from the centre of mass of the system.